PROMOVAREA LECTURII PENTRU COPII: PARADIGMA BIBLIOTECILOR GERMANE - TURVINENCO, Valentina (BIBLIOPOLIS, 2020)
The identity of the kids’ libraries is now a prioritaire subject. The article highlight the experience of the german libraries in the development of the freedom of expression and of the creativity of children which can be implemented in the libraries of the Republic of Moldova. The author proposes news ways of lecture stimulation